Rancang Bangun Sistem Informasi Helpdesk Ticketing Pelayanan Masyarakat Berbasis Web - Abu Bakar Riziq; Farizi Ilham; Fahmmi Firmansyah; Gumilang Ali Prayogi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
Public service is one of the primary functions of village government in fulfilling administrative needs and delivering information to citizens. However, the manual service process currently implemented at the Bojong Village Office causes several problems, including delays in handling reports, difficulties in retrieving data, lack of transparency in service status, and risks of archive loss. This study aims to design and develop a web-based Helpdesk Ticketing Information System to improve the effectiveness and efficiency of public services. The system development method used is the System Development Life Cycle (SDLC) with the Waterfall model, consisting of requirements analysis, system design, implementation, testing, and maintenance. The system was developed using PHP, MySQL, and Apache technologies. The results indicate that the system provides online complaint services, real-time report tracking, structured data management, and improved service transparency. The implementation of this system is expected to support the digital transformation of public services at the village level and increase community satisfaction with government services.